Influence of ionophore addition to a high-concentrate diet on net nutrient absorption in steers - D.L. Harmon; K.L. Gross; T.B. Avery (Kansas Agricultural Experiment Station Research Reports, 1987)
Feeding the ionophores monensin and lasalocid In a high-concentrate diet resulted in gut tissues utilizing less glucose. Monensin caused less urea to be recycled. The new, experimental ionophore (lCI 139603) resulted in an increased net absorption of acetate. Thus, ionophores may differ in how they execute their effects on feed efficiency.
Keywords: Cattlemen& #x27; s Day; 1987; Kansas Agricultural Experiment Station contribution; no. 87-309-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 514; Beef; Ionophore; High-concentration; Nutrient; Steers